Peran Pendidikan Agama Islam dalam Pembentukan Karakter Siswa di Era Digital - Ali Mahbub (Lisyabab : Jurnal Studi Islam dan Sosial, 2026)
The rapid development of digital technology presents significant challenges for education, particularly in shaping students’ character. Islamic Religious Education plays a fundamental role in preserving and transforming moral and spiritual values amid digital globalization. This study employs a qualitative library research approach by examining classical Islamic texts, contemporary academic works, reputable journals, and primary Islamic sources. The findings indicate that Islamic Religious Education is not merely the transmission of religious knowledge but a process of value internalization aimed at developing noble character. The integration of digital literacy with Qur’anic values such as truthfulness, responsibility, self-restraint, and spiritual awareness provides a foundation for nurturing moderate and integrity-based character in the digital era